Directly Printable Organic ASK Based Chipless RFID Tag for IoT Applications - Habib A; Ansar S; Akram A; Azam MA; Amin Y; Tenhunen H (SPOLECNOST PRO RADIOELEKTRONICKE INZENYRSTVI, 2022)
A chipless RFID tag with unique ASK encoding technique is presented in this paper. The coding efficiency is enhanced regarding tag capacity. The amplitude variations of the backscattered RFID signal is used for encoding data instead of OOK Strips of different widths are used to have amplitude variations. The ASK technique is applied using three different substrates of Kapton (R) HN, PET, and paper. To incorporate ASK technique, dual polarized rhombic shaped resonators are designed. These tags operate in the frequency range of 3.1-10.6 GHz with size of 70 x 42 mm(2). The presented tags are flexible and offer easy printability. The paper-based decomposable organic tag appears as an ultra low-cost solution for wide scale tracking. This feature enables them to secure a prominent position in the emerging fields of IoT and green electronics.